The High-Granularity Timing Detector for ATLAS at HL-LHC - Joaquim Pinol (Particles)
The increased particle flux expected at the HL-LHC poses a serious challenge for the ATLAS detector performance, especially in the forward region. The High-Granularity Timing Detector (HGTD), featuring novel Low-Gain Avalanche Detector silicon technology, will provide pile-up mitigation and luminosity measurement capabilities, and augment the new all-silicon Inner Tracker in the pseudo-rapidity range from 2.4 to 4.0. Two double-sided layers will provide a timing resolution better than 50 ps/track for MIPs throughout the HL-LHC running period, and provide a new timing-based handle to assign particles to the correct vertex. The LGAD technology provides suitable gain to reach the required signal-to-noise ratio, and a granularity of 1.3 × 1.3 mm2 (with 3.6 M channels in total). This paper presents the current status of the HGTD project with emphasis on the sensor development and module results.